Analysis of barriers in the process of applying for EU funds by public universities - Szczepaniak, Waldemar (Analiza barier w procesie aplikowania o środki unijne przez uczelnie publiczne, 2019)
The main objective of the study was to analyse and assess barriers hindering public universities from acquiring EU funds for their development. The study uses methods of literature sources analysis and quantitative research with the use of questionnaire distributed among managers of EU projects implemented in public technical universities. In the course of research it was concluded that internal barriers at university regarding the provision of funds necessary to finance own contribution and the insufficient number of adequately prepared staff are of key importance. The identification of the key barriers in obtaining EU funds should enable the necessary management actions to be taken at universities that increase their absorption capacity. As part of project management, the impact of the project environment should be taken into account and, by strengthening internal universities, it is necessary to effectively limit barriers to public universities applying for EU funds
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 223-232
Keywords: barriers; university environment; European Union projects; project environment; public universities; bariery; otoczenie uczelni; projekty unijne; środowisko projektowe; uczelnie publiczne